Improving Students' Literal Reading Comprehension through Direct Reading Thinking Activity - Lela, Nur; Baa, Sultan; Talib, Ahmad (Journal of Excellence in English Language Education, 2025)
This analysis aimed to evaluate whether the Direct Reading Thinking Activity (DRTA) improves students' ability to comprehend literal reading. The researcher utilized a pre-experimental design incorporating a single-group pre-test and post-test method. The study included 20 eighth-grade students from UPT SMPN 26 Kepulauan Selayar, selected using a total sampling technique. A reading comprehension assessment, focused on the literal understanding of recount texts, was employed as the research tool. The analysis of the pre-test and post-test data, using the significance test formula, showed a t-test value of 9.958, which was higher than the t-table value of 2.09302. This resulted in the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (H1). Further examination of the N-gain value placed the results in the "great" category. In conclusion, the use of the DRTA strategy significantly enhanced students' comprehension of critical components of texts, such as details, central themes, sequences, comparisons, cause-and-effect relationships, and character traits.